2014
DOI: 10.1016/j.jaac.2014.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Family-Focused Treatment for Adolescents and Young Adults at High Risk for Psychosis: Results of a Randomized Trial

Abstract: Objective Longitudinal studies have begun to clarify the phenotypic characteristics of adolescents and young adults at clinical high risk for psychosis. This 8-site randomized trial examined whether a 6-month program of family psychoeducation was effective in reducing the severity of attenuated positive and negative psychotic symptoms and enhancing functioning among individuals at high risk. Method Adolescents and young adults (mean 17.4±4.1 years) with attenuated positive psychotic symptoms, brief and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
143
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(147 citation statements)
references
References 34 publications
4
143
0
Order By: Relevance
“…For example, Miklowitz et al [11] reported a reduction in positive symptoms of psychosis as a result of family interventions in conjunction with skills-based training for adolescents at risk for psychosis. They noted that the combination of teaching strategies for stress reduction and problem solving with increased family support and improved communication proved to be beneficial.…”
Section: Need For Research On Early Intervention and Preventionmentioning
confidence: 99%
“…For example, Miklowitz et al [11] reported a reduction in positive symptoms of psychosis as a result of family interventions in conjunction with skills-based training for adolescents at risk for psychosis. They noted that the combination of teaching strategies for stress reduction and problem solving with increased family support and improved communication proved to be beneficial.…”
Section: Need For Research On Early Intervention and Preventionmentioning
confidence: 99%
“…This hope of early actionable concerns has led investigators to push prevention research toward earlier and earlier points of development. In schizophrenia research, children or adolescents are treated at the point when familial risk and early symptoms converge (Miklowitz et al, 2014). In ASD research, high-risk populations such as younger siblings are tracked during infancy to identify the first warning signs of atypical trajectory that may in turn be treated incrementally from low-to high-intensity approaches as the specific trajectory and response of the child becomes clearer (Green et al, 2013).…”
Section: Are Behavioral Disorders Similar To Cancers More Treatablementioning
confidence: 99%
“…Although this group is at much heightened risk, the majority do not go on to receive a diagnosis within 2 years. Some promising data have emerged for the use of cognitivebehavioral therapy, family therapy, atypical antipsychotic medications, and omega 3 fatty acids to prevent progression to schizophrenia, but these initial findings are quite mixed and await replication (Marshall and Rathbone, 2011;Miklowitz et al, 2014). One concerning finding is that while some could potentially be protected from progressing to a psychotic disorder, all of those who are treated are exposed to side effects of medications, most notably weight gain because of atypical antipsychotic medications including risperidone and olanzapine (Marshall and Rathbone, 2011).…”
Section: The Earlier the Better? Risk Vs Impairment When Contemplatinmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, one of the primary motivations behind these changes was to encourage intervention in the prodromal phase of psychiatric disorders, with the aim of preventing progression (4). Support for this paradigm came partly from encouraging studies of early intervention in youth at risk of schizophrenia and other neuropsychiatric disorders (5)(6)(7)(8)(9). To identify patients who might benefit from intervention, the NIMH called for research into physiological biomarkers for psychiatric disease, particularly into neuroimaging biomarkers.…”
mentioning
confidence: 99%